Pengaruh Video YouTube terhadap Keterampilan Menulis Teks Prosedur Siswa SMK - Siregar, Elvida; Pohan, Jusrin Efendi; Purba, Christin Agustina (GERAM, 2025)
This study aims to determine the effect of YouTube learning videos on the procedural writing skills of eleventh-grade students at SMK Pangeran Antasari. This research employs a descriptive quantitative approach using a true experimental design in the form of a pretest-posttest control group. The research design consists of two groups: the experimental group and the control group. The population was selected using probability sampling techniques, with students from the XI Busana class as the experimental group and students from the XI DKV class as the control group. Data collection was conducted through pre-test and post-test assessments for each class. The test used included assessment criteria for procedural text writing. Statistical data processing was performed using SPSS 25. The data showed normal and homogeneous distributions based on normality and homogeneity tests. The results of the independent t-test calculation indicated a significance value of 0.001 < 0.005, leading to the rejection of H0. The findings suggest that the use of YouTube learning videos in teaching procedural text writing to eleventh-grade vocational school students is more effective than conventional learning methods. This confirms a significant difference between using YouTube learning videos and conventional teaching methods.